2014
DOI: 10.1016/j.ejrnm.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Brain MR imaging abnormalities in pediatric patients after allogeneic bone marrow transplantation

Abstract: Objective: Our aim was to analyze brain MRI findings in pediatric patients who developed neurologic complications after allogeneic bone marrow transplantation. Materials and methods: This prospective study included 33 consecutive patients (age range from 3 to 18 years, mean 11.8 ± 5.1 years). They were referred to the MRI unit because of the neurological symptoms in the post transplant period. The underlying disorders included: non malignant hematological disorders (n = 20, 60.6%) and hematological malignancie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(43 reference statements)
0
1
1
Order By: Relevance
“…Compared with our study, Emad-Eldin & Abdel-Moeti [17] and Chaudhary et al [10], revealed higher incidence of post-HSCT intracranial hemorrhage in 6 and 3.4%, respectively. Moreover, Gerber et al [19], Emad-Eldin & Abdel-Moeti [17], and Hierlmeier et al [1] reported higher incidences of CVT of 4.6, 3, and 12.2%, respectively.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Compared with our study, Emad-Eldin & Abdel-Moeti [17] and Chaudhary et al [10], revealed higher incidence of post-HSCT intracranial hemorrhage in 6 and 3.4%, respectively. Moreover, Gerber et al [19], Emad-Eldin & Abdel-Moeti [17], and Hierlmeier et al [1] reported higher incidences of CVT of 4.6, 3, and 12.2%, respectively.…”
Section: Discussioncontrasting
confidence: 75%
“…Emad-Eldin & Abdel-Moeti's [17] study of 33 postallogenic HSCT patients with CNS complications revealed a 15% incidence of leukoencephalopathy; our study including both allogenic and autologous HSCT patients (525) shows a prominently lower incidence of 1.9%; all of them had undergone AlloSCT, and all of Literature stated that in patients undergoing HSCT, clinically significant cerebral bleeding was more common than symptomatic thrombotic events where both are important causes of morbidity and mortality [18]. Similarly, our study revealed a higher incidence of post-HSCT hemorrhagic episodes (1.5%) compared with CVT (cerebral venous thrombosis) episodes (0.9%).…”
Section: Discussionmentioning
confidence: 99%